Remedies available for aggrieved tenderers under PPR 2008 : a diagnostic analysis - Jilani, Md. Sharfuddin Khan (BRAC University, 2013)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.